2020
DOI: 10.3389/fcell.2020.00703
|View full text |Cite
|
Sign up to set email alerts
|

Bergenin as a Novel Urate-Lowering Therapeutic Strategy for Hyperuricemia

Abstract: Bergenin is a C-glucoside of 4-O-methyl gallic acid isolated from several medicinal plants and has multiple biological activities. The aim of this study was to assess the potential usefulness of bergenin in hyperuricemia. We found that bergenin reduced serum urate levels in hyperuricemia mice by promoting renal and gut uric acid excretion. Bergenin treatment increased Abcg2 expression both in the kidneys and intestine, while the expression of Slc2a9 was suppressed in the kidney and increased in the intestine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…In the intestine, the major site for the remaining 30% of urate excretion, the mechanisms of urate excretion are less well defined [38]. Urate transporters GLUT9 [41] and in particular ABCG2 [42] are highly expressed in intestinal epithelial cells and may thus represent interesting new pharmacological targets for the treatment of hyperuricemia [43][44][45][46][47]. Nonetheless, with regard to the sites of urate excretion (kidney & intestine) and the complex interplay of transporter-mediated excretion and reabsorption of urate in the kidney, the mechanisms of urate homeostasis are still not fully understood.…”
Section: Gout and Hyperuricemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In the intestine, the major site for the remaining 30% of urate excretion, the mechanisms of urate excretion are less well defined [38]. Urate transporters GLUT9 [41] and in particular ABCG2 [42] are highly expressed in intestinal epithelial cells and may thus represent interesting new pharmacological targets for the treatment of hyperuricemia [43][44][45][46][47]. Nonetheless, with regard to the sites of urate excretion (kidney & intestine) and the complex interplay of transporter-mediated excretion and reabsorption of urate in the kidney, the mechanisms of urate homeostasis are still not fully understood.…”
Section: Gout and Hyperuricemiamentioning
confidence: 99%
“…With regard to the treatment of cardiovascular comorbidities in hyperuricemia patients, it should be noted that blood pressure-lowering drugs such as the AT1 receptor blocker telmisartan have been shown to inhibit the transport activity of ABCG2 [75] thereby potentially exacerbating hyperuricemia in patients with a corresponding genetic predisposition. In view of the emerging role of ABCG2 and its importance for intestinal excretion of uric acid, it may in principle represent a novel pharmacotherapeutic target to lower uric acid levels [43][44][45][46][47]. As speculation, this may be accomplished by modifying ABCG2 expression and function in intestinal epithelial cells.…”
Section: Abcg2 Polymorphisms In Pediatric-onset Hyperuricemia and Early-onset Goutmentioning
confidence: 99%
“…Pifithrin-β hydrobromide, a specific and potent p53 protein inhibitor, activates the aryl hydrocarbon receptor to inhibit p53 and could reduce p53 protein expression. [24][25][26][27] Cells were treated with 0, 1, 10, and 50 nmol/L rapamycin (#S1842, Beyotime, China) and with 0, 10, and 20 µmol/L pifithrin-β hydrobromide (#HY-16702, MedChemExpress) to determine the optimal concentrations. A lentivirus for shRNA-mediated silencing of TSC1 (shTSC1, 5′-GACACACAGAATAGCTATG-3′) and a control lentivirus expressing negative control shRNA (shNC, 5′-TTCTCCGAACGTGTCACGT-3′) were constructed by GenePharma.…”
Section: Methodsmentioning
confidence: 99%
“…PPAR‐γ has been reported to protect neurons from ROS‐induce oxidative damage 48 and its antioxidant capacity was associated with NF‐κB suppression 49,50 . Simultaneously, several studies showed that bergenin acted as an agonist of PPAR‐γ when exerted its several biological activities 32,51–53 . Particularly, Wang et al demonstrated that bergenin could ameliorate colitis in mice through banding PPAR‐γ, then inhibiting the activation of NF‐κB in macrophage 53 .…”
Section: Discussionmentioning
confidence: 99%